Sensitivity Assessment on Satellite Remote Sensing Estimates of Primary Productivity in Shelf Seas - Xiaolong Zhao; Jianan Sun; Qingjun Fu; Xiao Yan; Lei Lin (Journal of Marine Science and Engineering, 2024)
The vertically generalized production model (VGPM) is one of the most important methods for estimating marine net primary productivity (PP) using remote sensing. However, different data sources and parameterization schemes of the input variables for the VGPM can introduce uncertainties to the model results. This study compared the PP results from different data sources and parameterization schemes of three major input variables (i.e., chlorophyll-a concentration (Copt), euphotic depth (Zeu), and maximum photosynthetic rate (PoptB)) and evaluated the sensitivity of VGPM in the Yellow and Bohai Seas on the inputs. The results showed that the sensitivity in the annual mean PP was approximately 40%. Seasonally, the sensitivity was lowest in the spring (35%), highest in the winter (70%), and approximately 60% in the summer and autumn. Spatially, the sensitivity in nearshore water (water depth